Arbitration in The Philosophy of Business Dispute Resolution in Indonesia - Cahyono, Joko (Yayasan Meira Visi Persada, 2025)
Resolving business disputes through arbitration is a wise thing to do in the business world, where disputes can arise from various reasons such as differences in interpretation of contract articulation, violation of contract rights, or disagreements when implementing agreements between parties. Arbitration is an option for dispute resolution outside the courts carried out by the parties involved with the assistance of an independent and neutral arbitrator or panel of arbitrators. In Indonesia, the Indonesian National Arbitration Board (BANI) is the most well-known and widely used arbitration institution in resolving business disputes. Although arbitration has advantages such as speed, lower costs, and the freedom to choose an arbitrator by the parties, there are still several challenges that need to be anticipated, such as the lack of public understanding of arbitration, the lack of understanding of consistency in arbitration regulations, and the lack of public trust in out-of-court settlements. To enhance the role of dispute resolution through arbitration, it is necessary to take steps such as improving the procedures and registration requirements and provisions of cases that can be handled at the arbitration institution, increasing the provision of qualified arbitrators in various fields that are needed, and increasing public trust in arbitration through comprehensive education programs. Thus, arbitration can be a practical solution and has the benefits of receiving justice in resolving national business disputes effectively, quickly, economically and still being able to establish relationships after the decision